NTA-enhanced Pb remediation efficiency by the phytostabilizer Athyrium wardii (Hook.) and associated Pb leaching risk. (May 2020) - Yu, Haiying; Zhan, Juan; Zhang, Qingpei; Huang, Huagang; Zhang, Xizhou; Wang, Yongdong; Li, Tingxuan
Abstract: Nitrilotriacetic acid (NTA), a biodegradable chelant, has been promoted to effectively assist Pb phytoextraction, while a few researches available on the phytostabilizer of Athyrium wardii (Hook.). In this study, two incubation experiments and a subsequent column experiment were conducted to investigate the effects of application of NTA on Pb availability in soils and Pb accumulation in A. wardii and associated leaching risk. The application of NTA significantly increased the exchangeable Pb and Pb bound to carbonates along with a decreased pH, leading to enhanced Pb availability in soils. It was more effective in enhancing Pb availability in soils by adding 2 mmol kg −1 NTA into soils at once for 7 d, thus demonstrating potential for enhancing Pb uptake by A. wardii . After the addition of 2 mmol kg −1 NTA for 7 d, Pb concentrations in roots of A. wardii was enhanced by 23.8%, along with 10.6% of increase for Pb accumulation in roots. No significant changes were observed for the biomass of A. wardii . Meanwhile, the available Pb and TCLP-extractable Pb in 0–20 cm soils increased by 11.1–23.4% and 7.1–31.2%, thus promoting Pb leaching in 0–20 cm soils. However, there were no changes for Pb leaching risk levels of 20–40 cm soils. No Pb was detected in the leachates from all columns. The application of 2 mmol kg −1 NTA at once for 7 d is therefore proved to show greater potential in enhancing Pb remediation efficiency by the phytostabilizer of A. wardii without increasing Pb leaching risk into groundwater. Highlights: NTA enhanced Pb availability by increasing exchangeable Pb and Pb bound to carbonates in soils. 2 mmol kg −1 NTA was more effective in enhancing Pb availability by adding into soils at once for 7 days. NTA application showed no significant effects on plant biomass of A. wardii. NTA application didn't increase Pb leaching risk into groundwater. NTA shows great potential in enhancing Pb remediation efficiency by A. wardii.